2017
DOI: 10.1371/journal.pone.0173930
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the diagnostic ability of vessel density and structural measurements of optical coherence tomography in primary open angle glaucoma

Abstract: PurposeTo compare the diagnostic abilities of vessel density measurements of the optic nerve head (ONH), peripapillary and macular regions on optical coherence tomography (OCT) angiography in eyes with primary open angle glaucoma (POAG) with that of the ONH rim area, peripapillary retinal nerve fiber layer (RNFL) thickness and the macular ganglion cell complex (GCC) thickness measurements.MethodsIn a cross sectional study, 78 eyes of 50 control subjects and 117 eyes of 67 POAG patients underwent vessel density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 29 publications
9
89
7
1
Order By: Relevance
“…Measurements of disc wiVD or cpVD correlated significantly with glaucoma severity, as previously reported. 26,27 In the present study, FAZ parameters also showed a significant correlation with glaucoma severity in that FAZ area and perimeter showed a significant negative correlation with cpRNFLT, mGCIPLT, and global/central VF MS (Table 4). Therefore, it is not surprising that there was a significant correlation between FAZ parameters and disc wiVD or cpVD, even though these measurements were derived from different retinal locations.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Measurements of disc wiVD or cpVD correlated significantly with glaucoma severity, as previously reported. 26,27 In the present study, FAZ parameters also showed a significant correlation with glaucoma severity in that FAZ area and perimeter showed a significant negative correlation with cpRNFLT, mGCIPLT, and global/central VF MS (Table 4). Therefore, it is not surprising that there was a significant correlation between FAZ parameters and disc wiVD or cpVD, even though these measurements were derived from different retinal locations.…”
Section: Discussionsupporting
confidence: 58%
“…23 At present, although it is known that both FAZ size and retinal VD measurements are altered in glaucoma patients, the relationship between microvasculature changes in the FAZ and VD measurements at various retinal locations is unknown. 12,13,[24][25][26][27] We hypothesized that clarification of this relationship would provide an additional insight into the clinical utility of FAZ size (area or perimeter) in the detection and possible monitoring of glaucoma. In the present study, we have, therefore, investigated the relationships between the FAZ size and VD measurements obtained with OCTA at different retinal locations, including the circumpapillary, parafoveal, and foveal regions in a series of healthy and glaucomatous eyes.…”
mentioning
confidence: 99%
“…In all of those areas, the diagnostic abilities increased with increasing severity of glaucoma [32, 34, 52]. This illustrated that an increasing severity of glaucoma was correlated with more pronounced vascular and structural damage.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly lower OCTA parameters (vessel density, blood flow index, and flow index) were found in glaucoma eyes in comparison with normal eyes in the peripapillary area [6, 16-50], the optic disc [19, 23, 25, 32, 36, 51-60] and the whole image macular area [16, 21, 32, 34, 36-38, 61-64]. In all of those areas, the diagnostic abilities increased with increasing severity of glaucoma [32, 34, 52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation